The role, involvement and function(s) of interleukin-35 and interleukin-37 in disease pathogenesis - Bello, Ramatu Omenesa; Chin, Voon Kin; Abd Rachman Isnadi, Mohammad Faruq; Abd Majid, Roslaini; Abdullah, Maizaton Atmadini; Lee, Tze Yan; Zakaria, Zainul Amiruddin; Hussain, Mohd Khairi; Basir, Rusliza (MDPI, 2018)
The recently identified cytokines—interleukin (IL)-35 and interleukin (IL)-37—have been described for their anti-inflammatory and immune-modulating actions in numerous inflammatory diseases, auto-immune disorders, malignancies, infectious diseases and sepsis. Either cytokine has been reported to be reduced and in some cases elevated and consequently contributed towards disease pathogenesis. In view of the recent advances in utilizing cytokine profiles for the development of biological macromolecules, beneficial in the management of certain intractable immune-mediated disorders, these recently characterized cytokines (IL-35 and IL-37) offer potential as reasonable targets for the discovery of novel immune-modulating anti-inflammatory therapies. A detailed comprehension of their sophisticated regulatory mechanisms and patterns of expression may provide unique opportunities for clinical application as highly selective and target specific therapeutic agents. This review seeks to summarize the recent advancements in discerning the dynamics, mechanisms, immunoregulatory and anti-inflammatory actions of IL-35 and IL-37 as they relate to disease pathogenesis.